New species of Mesopsyche Tillyard, 1917 (Mecoptera: Mesopsychidae) from the Triassic of northwestern China - Lian, Xinneng; Cai, Chenyang; Huang, Diying (Zootaxa, 2021)
Mesopsyche Tillyard, 1917 is an extinct genus of Mecoptera belonging to the long-proboscid-bearing Mesopsychidae, an adaptation probably associated with pollination of Mesozoic gymnosperms. Here, we describe two new species, Mesopsyche jinsuoguanensis sp. nov., from the Middle Triassic Tongchuan Formation in Shaanxi Province, and Mesopsyche liaoi sp. nov., from the Upper Triassic Huangshanjie Formation in the Xinjiang Uygur Autonomous Region of China. The new discoveries highlight the diversity of the Mesopsyche in the region during the Mesozoic.